Orexin-A Prevents Lipopolysaccharide-Induced Neuroinflammation at the Level of the Intestinal Barrier - Tunisi, Lea; Forte, Nicola; Fernández-Rilo, Alba Clara; Mavaro, Isabella; Capasso, Raffaele; D'Angelo, Livia; Milić, Nataša; Cristino, Luigia; Di Marzo, Vincenzo; Palomba, Letizia (Frontiers in Endocrinology, 2019)
In states of intestinal dysbiosis, a perturbation of the normal microbiome composition, the intestinal epithelial barrier (IEB) permeability is increased as result of disruption of the epithelial tight junction protein network among which occludin is mostly affected. The loss of IEB integrity promotes endotoxemia, that is bacterial lipopolysaccharide (LPS) translocation from the intestinal lumen to the circulatory system. This condition induces an enhancement of pro-inflammatory cytokines, which leads to neuroinflammation through the gut-brain axis. Orexin-A (OX-A), a neuropeptide implicated in many physiological functions and produced mainly in the brain lateral hypothalamic area, is expressed also in several peripheral tissues. Orexin-producing neurons have been found in the myenteric plexus to project to orexin receptor 1 (OX-1R)-expressing enterocytes of the intestinal villi. In the present study we investigated the protective role of OX-A against LPS-induced increase of IEB permeability and microglia activation in both an in vivo and in vitro model of gut-brain axis. By exploiting biochemical, immunocytochemical, immunohistochemical and functional approaches, we demonstrated that OX-A preserves the IEB occludin expression thus preventing endotoxemia and consequent neuroinflammation.